Suitable factorization of the total intersubband scattering rates for efficient calculation of the current densities and gain characteristics in quantum cascade lasers - Kurlov, S.S.; Semtsiv, M.P.; Zhuchenko, Z.Ya.; Tarasov, G.G.; Masselink, W.T. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
Suitable factorization of the intersubband scattering rates is performed for the temperature-dependent electron transport model of mid-infrared quantum cascade lasers (QCL). In this case, the total intersubband scattering rate is presented as a sum of individual processes: longitudinal optical phonon, roughness interface, and acoustic phonon scatterings. The individual scattering rate is reduced to a product of the overlap integral for the squared moduli of the envelope functions and the temperature factor that depends on the transition energy and material. This presentation significantly reduces computational efforts in comparison with the ab initio models of full quantum transport in QCL, preserving good agreement between the theory and experiment, as well.